Storytelling Branding: Strategi Sampurasun Bandung dalam Meningkatkan Literasi dan Pelestarian Budaya Lokal - Mohamad Hadi Prasetyo (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to analyze the storytelling strategy of branding carried out by Sampurasun Bandung in improving cultural literacy and preserving local culture in the digital era. Using a qualitative descriptive method through a case study approach, this study explores how cultural narratives, local symbols, and the use of digital media are used to build brand identity while strengthening cultural awareness among the public, especially the younger generation. The research data was obtained through observation of Sampurasun Bandung's official social media, digital content analysis, in-depth interviews with managers and related communities, and documentation of cultural-based offline activities. The results of the study show that the application of consistent and authentic branding storytelling, both through visual content, historical narratives, and community activities, is able to increase people's cultural literacy and make a real contribution to the preservation of Sundanese culture. In addition, this strategy also strengthens audience engagement and loyalty to the brand. The findings of this study enrich the literature on culture-based branding and provide strategic recommendations for creative business actors in integrating local cultural values in a sustainable manner.